Implementation of Video Capture and Playback in Mobile Systems - Sanket Dessai; K Ramakrishna (International Journal of Reconfigurable and Embedded Systems (IJRES), 2013)
Mobile phones are backbone of the mobile communications and have experienced fastest growing segment in the consumer market. In the 3G and 4G mobiles, video recording is an essential entertainment features so the user can record and play the video within the mobile phone. In this paper, video capture and playback implementation had been carried out by integrating the camera module to the GSM phone. An alaysis of the video processing had been carried out. Image sensor and LCD module had been interfaced with the base band processor through the video processor. To interface the different module necessary PCB schematic diagram had been arrived. Software implementation had been carried out for the Human Machine Interface for various settings of the camera module, which is integrated with the video processor. The developed playback system had been tested for the various senerious. In this video has been captured through the camera sensor and at the time of playback measured the resolution, power consumption and image transfer rates of the various modules used in the developed camera phone.